THE MAGIC OF AYURVEDA IN DENTISTRY: A REVIEW - Shriya Khera,; Sunita Gupta, (International Journal of Ayurveda and Pharma Research, 2020)
Ayurveda is about 3000 years old and is increasingly becoming popular. It is a holistic treatment modality which has been successfully used to cure various oral and systemic diseases. The role of Ayurveda and its beneficial effects have also been extensively seen in the maintenance of oral health. Numerous Ayurvedic herbs have been listed in different manuscripts along with their beneficial effects. The present review focuses on various Ayurvedic herbs used in dentistry with their promising effects on oral cavity i.e., strengthening the gingival and periodontal health, preventing tooth decay, eliminating halitosis and in management of various oral mucosal lesions. The numerous beneficial effects of these phytochemicals have been listed in detail. However, many of these Ayurvedic herbs are still under study and their beneficial roles are yet to be stated.